The SMEDIS database and validation exercise. (1st January 2001) - Carissimo, B.; Jagger, S.F.; Daish, N.C.; Halford, A.; Selmer-Olsen, S.; Riikonen, K.; Perroux, J.M.; Wurtz, J.; Bartzis, J.G.; Duijm, N.J.; Ham, K.; Schatzmann, M.; et al.
SMEDIS is an ongoing research project funded by the European Union under the Environment and Climate Research Programme for the period 1996-1999. The project is coordinated by the Health and Safety Executive (HSE, UK) with two other main partners Cambridge Environmental Research Consultants (CERC, UK) and Electricite de France (EDF, France). Ten additional partners from across Europe are also participants in the project. The main objective of the project is to develop a methodology for the evaluation of dense gas atmospheric dispersion models used in the study of accidental releases of explosive or toxic materials. This evaluation is composed of a scientific assessment of each model, together with a validation by comparison with available experimental data. This paper describes more specifically the database constructed, and the validation performed by the participants involved in the project. Preliminary results indicate that the restriction for arcwise concentrations leads to an optimistic view of model performance when complex effects are present and that, in general, statistical performance is better for more sophisticated models.